Role of leucocytosis, hyperbilirubineamia, decreased mean platelet volume and increased international normalized ratio in prediction of complicated appendicitis - Soni, Amit; Pipal, Dharmendra K.; Bhargava, Anupam; Jain, Saurabh; Singh, Yatindra; Sahu, Vinod; ., Jaypal; ., Omprakash; Joshi, Manoj; Pipal, Vibha R. (International Surgery Journal, 2021)
Background: A diagnostic approach for complicated appendicitis is still controversial. We analyzed the preoperative laboratory markers that may predict complicated appendicitis. Methods: To study the role of leukocytosis, hyperbilirubinemia, decreased mean platelet volume (MPV) and increased international normalized ratio (INR) in the prediction of complicated appendicitis. Total 60 patients were enrolled and divided them into 2 groups, un-complicated (AUA) and complicated (ACA) acute appendicitis, each having 30 cases. Results: Total leucocyte count (TLC) >10000 mm³ was found in 70% of AUA cases and 80% of ACA cases serum bilirubin >1 mg/dl was found in 66.67% of AUA cases and 80 % of ACA cases. MPV<7.6 fL was found in 60% of AUA and 80% of ACA cases INR >1.2 was found in 20 % of AUA and 40% of ACA cases. TLC >10000/mm³, serum bilirubin >1 mg/dl and MPV <7.6 fL was found in 46.67% of AUA cases and 70 % of ACA cases. Conclusions: Total leucocyte count, serum bilirubin and mean platelet volume have a predictive potential for the diagnosis of complicated appendicitis.